Discrepancy in the Value of Labor and the Implications for Economic Inequality - Indragus Pangestu; Zuly Qodir; Virdika Rizky Utama (JSW (Jurnal Sosiologi Walisongo), 2023)
Discrepancy in the value of labor is a discrepancy between the price of work expressed in money or wages with the necessities of a decent life. This discrepancy results in an accumulation of income that leads to economic inequality. The aim of the research is to find out the discrepancy in the value of labor experienced by workers and its impact on economic inequality. This research was conducted in Yogyakarta considering that this city has the highest level of economic inequality and is one of the regions with the lowest minimum wage in Indonesia. This research method is descriptive qualitative by looking at the difference in value between decent living needs and district/city minimum wages in Yogyakarta Province. The data includes district/city minimum wages, the cost of living necessities, and main employment status. The results of this study show that there is a discrepancy in the value of labor in Yogyakarta in 2022 and 2023. This discrepancy can be seen through the difference between the necessities of life and the minimum wage of IDR 858,281- IDR 1,801,059. In addition, the discrepancy in the value of labor encourages economic inequality as a result of the accumulation of income received by owners of capital and the exploitation of labor experienced by workers.